Про нелінійні диференціально-операторні рівняння в банахових просторах із відображеннями псевдомонотонного типу. Частина I - Melnik, V. S.; Toskano, L. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
The proof for the existence theorem is constructed using Galyorkin's mehod. The functional-analythic properties of the solutions to nonlinear differential-operator equations in banach spaces with λ-pseudomonotonous mapping are investigated.